Una aproximación al estudio de las arengas fallidas: Livio, Lucano y Silio Itálico - Jesús Bartolomé Gómez (Talia dixit, 2015)
The failed battle exhortation speeches have not been so far analyzed in a systematic way, so this paper proposes a critical approach to this kind of speech both in Roman historiography and epic. Since the number of examples is not very high, we will study all of them in order to show the value and function they fulfill. Authors (Livy, Lucan and Silius Italicus) have been selected regarding to the thematic and intertextual relationships their works have.